Profitability, analysis of climate-smart agriculture practices among smallholder farmers: Evidence from cowpea, millet, and groundnut growers in Senegal. - Worou, Nadine; Thiaw, Moussa; Mathew Akinsey, Folorunso; Wane, Abdrahmane; Whitbread, Anthony (International Livestock Research Institute, 2025)
This poster highlights the economic benefits of adopting climate-smart agriculture (CSA) for smallholder farmers in Senegal, comparing the performance of CSA practices with that of ‘traditional’ farming methods for millet, cowpea and groundnut in six regions (Kaffrine, Louga, Thiès, Kaolack, Tambacounda, Fatick). The analysis, based on surveys of 873 households and a cost-benefit assessment (including net present value/NPV), shows that CSA improves yields for millet and cowpea, with a positive but more moderate effect for groundnuts. Economically, cowpea emerges as the most profitable crop in the long term (positive NPV), followed by groundnuts with moderate profitability, and millet appears promising depending on the context. However, the poster highlights barriers to adoption: high initial costs, labour requirements, and low uptake of specific practices (e.g. micro-dosing of fertilisers) . It recommends integrating appropriate financing mechanisms, labour-saving technologies and targeted training to overcome these obstacles. The results provide useful evidence to support national adaptation policies, in particular Senegal's ‘adaptation pathways’ for 2050.